Broadening inclusivity at sea - Wang, Lu; Adams, Caitlin; Fundis, Allison; Hsiao, Janet; Machado, Casey; Malik, Mashkoor; Quadara, Rachel; Rodriguez, Coralie; Soule, Adam; Suhre, Kelley; Wu, Liang; Elmore, Aurora C. (Frontiers in Marine Science, 2024)
Ocean sciences in the U.S. remains a field with one of the lowest rates of diversity, having disproportionately low representation from marginalized groups, including Black, Asian, LatinX, Indigenous, and other people of color; LGBTQIA+ individuals; disabled persons; women; those with neurological differences; and those from low-income groups. With equity and inclusion in mind, recent efforts have been made to increase the number of ocean science professionals from marginalized groups through multiple entry points, including internships. However, there still exists a large gap between the diversity found in the general population and the diversity within ocean sciences. Perhaps one reason why this field continues to have lower diversity owes to the unique component of many oceanographic careers, which continues to present an especially high barrier for marginalized groups: participating in sea-going research expeditions. Herein, we have synthesized possible ways to prioritize the physical and emotional safety of marginalized ocean science professionals participating in a research expedition, including guidance on preparation, implementation, and providing support post-cruise. These suggestions are intended to be useful for the broader oceanographic research community to consider the safety and well-being of individuals from marginalized groups at sea, since the field of ocean sciences - like all fields - would greatly benefit from increased representation and diversity.